2017
DOI: 10.3892/etm.2017.4581
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two-dimensional strain echocardiography for quantifying right ventricular function in patients with pulmonary arterial hypertension

Abstract: Abstract. The aim of the current study was to evaluate the use of two-dimensional strain echocardiography (2DS) in quantifying right ventricular (RV) function in patients with pulmonary arterial hypertension (PAH). A total of 41 patients with PAH and 40 healthy control patients were recruited to the study. 2DS was used to determine the strain (ε) and strain rate (SR) of basal, middle and apical segments of the RV free wall. The aforementioned indicators were compared with measurements of RV function taken by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Addetia K, et al [ 13 ] used RV systolic parameters, such as basal and mid-RV dimensions, length, TAPSE, tissue Doppler S′ velocity, and RV longitudinal strain in normal subjects, and found that RV strain was believed to better represent RV systolic function than longitudinal measurements. Previous studies mainly focused on some diseases may damage RV functions directly, such as pulmonary arteries hypertension [ 14 , 15 ], atrial septal defect [ 16 ], tetralogy of Fallot [ 17 , 18 ], severe tricuspid regurgitation [ 19 ], and so on. Although there were some studies on RV function, the information on RV systolic and diastole functions in T2DM patients using RV layer specific GLS and GLSr was still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Addetia K, et al [ 13 ] used RV systolic parameters, such as basal and mid-RV dimensions, length, TAPSE, tissue Doppler S′ velocity, and RV longitudinal strain in normal subjects, and found that RV strain was believed to better represent RV systolic function than longitudinal measurements. Previous studies mainly focused on some diseases may damage RV functions directly, such as pulmonary arteries hypertension [ 14 , 15 ], atrial septal defect [ 16 ], tetralogy of Fallot [ 17 , 18 ], severe tricuspid regurgitation [ 19 ], and so on. Although there were some studies on RV function, the information on RV systolic and diastole functions in T2DM patients using RV layer specific GLS and GLSr was still limited.…”
Section: Discussionmentioning
confidence: 99%